2013
DOI: 10.1063/1.4840075
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sensitivity and contrast with bimodal atomic force microscopy with small and ultra-small amplitudes in ambient conditions

Abstract: Here, we introduce bimodal atomic force microscopy operated with sub-nm and ultra-small, i.e., sub-angstrom, first and second mode amplitudes in ambient conditions. We show how the tip can be made to oscillate in the proximity of the surface and in perpetual contact with the adsorbed water layers while the second mode amplitude and phase provide enhanced contrast and sensitivity.\ud Nonlinear and nonmonotonic behavior of the experimental observables is discussed theoretically with a view to high resolution, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…[11][12][13] It was shown that the small oscillation of the second flexural mode could be used to increase sensitivity to material properties. [14][15][16][17] Several groups have applied this technique to biological samples, including antibodies 13 and proteins. 11 Schwenk and coworkers used bimodal AFM to increase the contrast stemming from magnetic interaction with a ferromagnetic tip.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] It was shown that the small oscillation of the second flexural mode could be used to increase sensitivity to material properties. [14][15][16][17] Several groups have applied this technique to biological samples, including antibodies 13 and proteins. 11 Schwenk and coworkers used bimodal AFM to increase the contrast stemming from magnetic interaction with a ferromagnetic tip.…”
mentioning
confidence: 99%
“…12 More recently, Santos and coworkers have started to consider the advantages of small oscillations in both flexural modes. 15,21 In order to optimize the bimodal measurements for atomic resolution in both modes, data should be acquired with small amplitudes in both the first and second flexural modes. 15 This requires the use of a much stiffer sensor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has several configurations depending on the feedback schemes [16][17][18][19][20][21][22][23][24]. In the first bimodal AFM configuration (bimodal AM) [15,16], the feedback acts on the amplitude of the first mode by keeping it at a fixed value during imaging while the second mode operates in an open loop.…”
Section: Introductionmentioning
confidence: 99%
“…The single frequency virial that controls the phase shift might undergo transitions in sign while the average force (modal virial) remains positive (negative). Multifrequency atomic force microscopy (AFM) is an emerging 1,2 branch of AFM where two or more frequencies 3,4 are externally excited in order to map material composition, [5][6][7] enhance resolution 8 and sensitivity, [9][10][11] and quantify material properties [12][13][14] with gentle forces. The theory that controls the response of the cantilever while simultaneously exciting several frequencies and modes however is still emerging 12,15,16 and might result complex.…”
mentioning
confidence: 99%